Comparative study of porphyrin derivatives in monolayers at the air-water interface and in langmuir-blodgett films - Ghosh, Amrita; Mahato, Prasenjit; Choudhury, Sipra; Das, Amitava (Thin Solid Films, 2011)
The orientation and aggregation of various porphyrin derivatives at the air–water interface and in Langmuir–Blodgett films were investigated. Monolayer properties of these molecules, where long alkyl chain(s) were covalently bound through different functionality of varying hydrophilicity were studied by measuring surface pressure area isotherms. Such derivatives, where ether functionality (functionalities) was (were) used for linking long alkyl chain(s), did not form uniform monolayer; instead they were found to form multilayer clusters or aggregates on the water surface. On the other hand, porphyrin derivative functionalized at the four peripheral phenyl rings with eight hexadecyl ether chains formed stable spherical vesicles when deposited on mica. Tetra N-alkyl pyridinium porphyrins with long alkyl chain were found to form various phases on the water surface. Evidence of transition from horizontal orientation to vertical orientation of porphyrin rings of porphyrin molecules having C14 chains was observed. This type of transition was lost with the porphyrin molecule with a relatively smaller chain (C8).